2009
DOI: 10.1188/09.onf.709-715
|View full text |Cite
|
Sign up to set email alerts
|

Delay in Diagnostic Testing After Abnormal Mammography in Low-Income Women

Abstract: Purpose/Objectives To identify factors associated with diagnostic delay after an incomplete or abnormal mammogram among women participating in a state mammography screening program. Research Approach Retrospective case-control design using bivariate and multivariate logistic regression analyses to explore the associations between age, race, ethnicity, marital status, breast cancer history, and self-reported breast symptoms and delay. Setting A statewide program of free screening mammography for women who a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…For example, women who experienced a delay between the time of mammogram and diagnosis or last diagnostic test ruling out cancer were found to be more likely to be Black than White (odds ratio 1.45; 95% confidence interval = 1.13, 1.85). (35)…”
Section: Discussionmentioning
confidence: 99%
“…For example, women who experienced a delay between the time of mammogram and diagnosis or last diagnostic test ruling out cancer were found to be more likely to be Black than White (odds ratio 1.45; 95% confidence interval = 1.13, 1.85). (35)…”
Section: Discussionmentioning
confidence: 99%
“…5, 6 Compared with whites, black and Hispanic women have lower likelihood of receiving follow-up for abnormal mammography. 716 Little data exist on racial/ethnic disparities in time to follow-up of abnormal fecal occult blood testing or fecal immunochemical tests (FOBT/FIT). 17 Comparisons across cancers may suggest processes that promote timely resolution of positive screening tests.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has found that race/ethnicity, age ≥ 40 years, lower levels of education and median household income, and lack of insurance, solely or in combination, were predictors of delays in diagnostic follow-up from abnormal MS in African-American women [4][5][6][7]. In Fair et al study of 76 medically-underserved women age >40 years with inadequate follow-up imaging or biopsy (≥ 6 months since mammogram results), 48% of African-American women perceived low benefits and high barriers to follow-up from screening and care, and reported a decrease in internal health locus of control.…”
Section: Introductionmentioning
confidence: 99%